The Influence Of Work Motivation On Teacher Performance In Realizing Effective Educational Goals - Pimpin Nursalihin (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This research aims to determine the effect of work motivation on teacher performance in realizing effective educational goals. By using a quantitative approach and correlational research type, a survey design was applied in this research to collect data through distributing questionnaires. The population of this research is all junior high school teachers in Mesjid Raya District, totaling around 85 people. Data was collected using a questionnaire consisting of two parts, namely the work motivation scale and the teacher performance scale, which have been tested for validity and reliability. The analysis technique used is descriptive statistics to describe the characteristics of the data, as well as the Spearman's rho test to examine the relationship between work motivation and teacher performance. The research results show that there is a significant influence between work motivation and teacher performance in realizing effective educational goals, with a correlation coefficient of 0.566, which shows a moderate positive relationship between these two variables. These findings indicate that increasing work motivation can improve teacher performance, which ultimately contributes to achieving educational goals more effectively. Keywords: motivation, work, performance, teacher, education